A New Model of Batch Biodrying of Sewage Sludge, Part 2 Model Calibration and Validation - Huilinir-Curio, C; Perez-Aviles, J (Taylor and Francis Inc., 2017)
The calibration and validation of a new model of batch biodrying of sewage sludge are presented. The calibration was performed with experimental data from the literature, while the validation was performed with new experimental data. The model was successfully calibrated with experimental data, with the values of parameters falling in the range of values reported. The new model also represented the behavior of the experimental data for all the variables measured, showing that it is robust and valid for the simulated conditions. Simulations showed that continuous high aeration increased the efficiency of the process. © 2017 Taylor & Francis.